A case report of the diagnosis and management of acromegaly in routine periodontal examination - Choo, Hui Jia Sophia; Chee, Hoe Kit (Journal of Oral Diagnosis, 2023)
Introduction: Acromegaly is a rare endocrine disorder, presenting with orofacial mani-festations during its early stages. Timely diagnosis is often not made as these symptoms overlap with other oral diseases. Objective: The objective of this case report is to describe an unusual detection of acromegaly in a dental setting and to provide a checklist for referral upon suspicion of acromegaly. Materials and Methods: This case report describes the orofacial presentation and management of a 44-year-old Chinese man, initially referred for periodontal management. He presented with Localised stage II Grade A periodontitis, class III malocclusion, mandibular prognathism, and large mandibular interproximal gaps. Results: A provisional diagnosis of acromegaly was made, and the patient was referred to the Department of Endocrinology. Conclusion: Dental practitioners can pick up patients with undetected acromegaly with early orofacial changes during routine dental visits according to a simple proposed checklist.